Understanding Customer Fatigue in Digital Marketing: A Stimulus–Organism–Response Perspective on Social Media Fatigue and Behavioral Consequences - Chandra Hadi Prayoga; Wiwiek Rabiatul Adawiyah; Najmudin Najmudin; Sudarto Sudarto (Faculty of Economics and Business Universitas Jenderal Soedirman, 2026)
Abstract Social media has become a central channel in digital marketing management for building customer engagement and sustaining long-term relationships. The intensity of interactions, dense information flows, and psychological pressures embedded in social media environments have introduced new challenges in the form of social media fatigue, which may undermine the quality of customer experience and engagement. This study aims to analyze the psychological mechanisms that link pressures in social media environments to various customer behavioral responses within the context of digital marketing. Adopting the Stimulus–Organism–Response (S-O-R) framework, this study positions Fear of Missing Out, privacy concern, and information overload as stimuli in the digital marketing environment; social media fatigue as the customer’s internal state; and discontinuance of usage, interaction engagement decrement, and fake news sharing as customer behavioral responses. Data were collected through a survey of 155 active social media users and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that Fear of Missing Out, privacy concern, and information overload significantly contribute to increased social media fatigue. Furthermore, social media fatigue is shown to increase tendencies toward usage discontinuance, reduced interaction engagement, and the sharing of unverified information. These results highlight the role of social media fatigue as a key mechanism linking pressures in digital marketing environments to diverse customer behavioral outcomes. This study contributes theoretically by extending the application of the S-O-R framework within the digital marketing literature and offers practical implications for platform managers and digital marketing practitioners in managing customer experience, sustaining engagement, and mitigating customer fatigue risks in increasingly complex social media ecosystems.